PERLINDUNGAN DAN PENEGAKAN HAK ASASI MANUSIA DI INDONESIA - Vanessa Mathilde Harum; Moody Rizqy Syailendra (Jurnal Hukum Adigama, 2022)
Right is a normative element that has been attached to every human being since he was born which in its application is within the scope of equal rights and freedom rights and is related to interactions between individuals or agencies. Human rights as rights that are inherent in the nature and existence of humans. Human rights can be formulated as rights attached to the biological nature of humans. This right belongs to humans solely as human beings, not because of a gift from the people or a gift from the state. So human rights do not depend on the recognition of other human beings, other people, or other countries. The issue of human rights is something that is often discussed and given more attention in this reformation era. Human rights are highly respected and paid more attention to in the reform era than in the previous era. It should be remembered that in terms of fulfilling rights, we do not live alone and we live in social relations with other people. Do not let us commit human rights violations against other people in our own efforts to obtain or fulfill human rights. Nevertheless human rights violations still occur frequently, reflected in the existence of subordination to women, violence, rape, and exploitation of children.